The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1038/ncb2372
|View full text |Cite
|
Sign up to set email alerts
|

K-fibre minus ends are stabilized by a RanGTP-dependent mechanism essential for functional spindle assembly

Abstract: Chromosome segregation requires the formation of K-fibres, microtubule bundles that attach sister kinetochores to spindle poles. Most K-fibre microtubules originate around the chromosomes through a non-centrosomal RanGTP-dependent pathway and become oriented with the plus ends attached to the kinetochore and the minus ends focused at the spindle poles. The capture and stabilization of microtubule plus ends at the kinetochore has been extensively studied but very little is known on how their minus-end dynamics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
118
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(128 citation statements)
references
References 52 publications
10
118
0
Order By: Relevance
“…These data provide a molecular link between the chromosomal MTs and the K-fibers that goes beyond previous observations of the formation of acentrosomal MTs at the kinetochores (Khodjakov et al, 2003;Maiato et al, 2004). Interestingly, the distinct spindle MT subclasses have distinct dynamic properties, (Rizk et al, 2009), and functional studies have shown that MCRS1 could have a role in the regulation of Kfiber minus-end stability (Meunier and Vernos, 2011).…”
Section: Kidsupporting
confidence: 51%
See 2 more Smart Citations
“…These data provide a molecular link between the chromosomal MTs and the K-fibers that goes beyond previous observations of the formation of acentrosomal MTs at the kinetochores (Khodjakov et al, 2003;Maiato et al, 2004). Interestingly, the distinct spindle MT subclasses have distinct dynamic properties, (Rizk et al, 2009), and functional studies have shown that MCRS1 could have a role in the regulation of Kfiber minus-end stability (Meunier and Vernos, 2011).…”
Section: Kidsupporting
confidence: 51%
“…Importin-b (Meunier and Vernos, 2011) Binds and protects chromosomal MT minusends (Meunier and Vernos, 2011) n.d.…”
Section: Mcrs1mentioning
confidence: 99%
See 1 more Smart Citation
“…In mammalian somatic cells, Ran GTPase activity promotes microtubule nucleation at kinetochores (33), and Ran effectors such as microspherule protein 1 and γ-TuRC also function in K fibers (34,35). As TACC3 is also a target of the Ran GTPase system (20), it may coordinate with Ran to regulate acentrosomal microtubules for kinetochore capture.…”
Section: Tacc3-dependent Acentrosomal Microtubule Nucleation Is Requimentioning
confidence: 99%
“…In an analogous manner, MCAK interacts with the EB1-dependent plus-tip tracking kinesin 8 Kif18b, and this interaction is required for robust MT depolymerization in cells (52,53). The specificity of MCAK as a plus-end depolymerase could be further regulated by the minus-end-binding proteins patronin/CAMSAP (54 -56) and MCRS1 (57), which block MCAK activity at the MT minus-end to enhance MT stability (Fig. 2G).…”
Section: Adding Complexity Via ؉ Tipsmentioning
confidence: 95%